1979
DOI: 10.1111/j.1365-2125.1979.tb00995.x
|View full text |Cite
|
Sign up to set email alerts
|

The gastrointestinal absorption of PRD‐92 Ea, a new anti‐allergy drug.

Abstract: 1 The absorption of PRD‐92 Ea, a new anti‐allergy drug, was studied in volunteer subjects. 2 The 14C‐labelled drug was administered orally and the radioactivity measured in plasma, urine and faeces. 3 Mean peak plasma concentration was 3.3 micrograms/ml, with a concentration of over 1 micrograms/ml maintained 4 h after administration. 4 The mean plasma half‐life (T 1/2) was 114 min. 5 The mean percentage recovery in the urine was 9.5%. 6 Oral administration leads to significant and sustained plasma concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1985
1985

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This com pound has the additional property of being well absorbed following oral administration in rat and monkey [4,5,10] and in man [6]. On the basis of in vitro studies, it has been reported that Ea is an antagonist of several putative mediators of asthma and in flammation [8], indicating that this com pound may be grouped with other anti allergy drugs having a mixed antagonist/anti allergy action, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This com pound has the additional property of being well absorbed following oral administration in rat and monkey [4,5,10] and in man [6]. On the basis of in vitro studies, it has been reported that Ea is an antagonist of several putative mediators of asthma and in flammation [8], indicating that this com pound may be grouped with other anti allergy drugs having a mixed antagonist/anti allergy action, e.g.…”
Section: Introductionmentioning
confidence: 99%